Using Story to Understand Teacher Knowledge (LEARNing Landscapes, 2018)
The knowledge preservice teachers bring is experiential, grounded in stories they’ve lived and told. Because of the way story captures experience, it’s valuable in the learning-to-teach process. In this commentary, we return to narrative research we completed to consider the stories preservice teachers tell in learning to teach. We explore what we know about teaching from stories we’ve told and consider how story positions teacher educators. These explorations provide narrative insights that guide us in developing stronger teachers. These stories allow us to build on teacher knowledge as well as disrupt preconceptions and beliefs within their teacher education.
Keywords: narrative research; teacher knowledge; narrative understandings; teacher stories